Plastic Waste Management in Indonesia: Current Legal Approaches and Future Perspectives - Maskun Maskun; Hanim Kamaruddin; Farida Pattitingi; Hasbi Assidiq; Siti Nurhaliza Bachril; Nurul Habaib Al Mukarramah (Hasanuddin Law Review, 2023)
The ever-increasing domestic consumption of plastic products and materials has forced Indonesia to propel forward the means and approaches in dealing with their disposals. Despite the presence of numerous legal instruments serving as basis justifying actions to deal with plastic waste, Indonesia is still nowhere near success in tackling the issue of mismanagement. This article is devoted to normatively analyze various legal approaches used to govern plastic waste management Indonesia, and to unravel issues related to such approaches. It is carried out using normative-legal research methods in which various legal instruments and other secondary legal materials are analyzed descriptively to point out the emerging legal issues. The main findings reveal that laws and regulations as well as public policies that serve as legal basis and approach to deal with plastic waste governance in Indonesia still possess some weaknesses. Further examinations suggest the needs for improvement in some legal aspects from which some new perspectives could then be shaped to envisage future actions.